IDENTIFICATION OF STUDENT’S LEXICAL ERROR IN TRANSLATING ENGLISH TEXT INTO INDONESIAN - Abdul Rohim; Aidil Syah Putra (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
This research identifies students’ lexical errors in translating English text into Indonesian at Open University (Universitas Terbuka). The lexicon is essential in a translation. A good and acceptable translation should be able to successfully render the message of the source language into the target language by using the appropriate lexicon. The incorrect lexical choice will distort the source language's message. A translation test was administered to 35 students as part of the data collection process. The finding shows some students wrongly order the word in a sentence as the  result  of  word  by  word  translation  and  they  translate  it  using  dictionary and translation  machine like  Google  translate  so  that  it  still  has  errors  in  sentence  or  word. In addition, some of the students translate English text into Indonesian word by word. So that the translation did not correspond with the meaning of the text. Even though they used a dictionary, but they did not understand the text perfectly.